Label-free Electrochemical Impedance Spectroscopy Aptasensor for Ultrasensitive Detection of Lung Cancer Biomarker Carcinoembryonic Antigen - Wang, Yawei; Chen, Lei; Xuan, Tiantian; Wang, Jian; Wang, Xiuwen (Frontiers in Chemistry, 2021)
In this work, an integrated electrode system consisting of a graphene working electrode, a carbon counter electrode and an Ag/AgCl reference electrode was fabricated on an FR-4 glass fiber plate by a polyethylene self-adhesive mask stencil method combined with a manual screen printing technique. The integrated graphene electrode was used as the base electrode, and AuNPs were deposited on the working electrode surface by cyclic voltammetry. Then, the carcinoembryonic antigen aptamer was immobilized using the sulfhydryl self-assembly technique. The sensor uses [Fe(CN)6]3−/4− as a redox probe for label free detection of carcinoembryonic antigen based on the impedance change caused by the difference in electron transfer rate before and after the binding of carcinoembryonic antigen aptamer and the target carcinoembryonic antigen. The results showed a good linear relationship when the CEA concentration is in the range of 0.2–15.0 ng/ml. The detection limit was calculated to be 0.085 ng/ml (S/N = 3).